Power Metering: History and Future Trends - Garcia, Fernando Deluno [UNESP]; Marafao, Fernando Pinhabel [UNESP]; Souza, Wesley Angelino De; Silva, Luiz Carlos Pereira Da (Institute of Electrical and Electronics Engineers (IEEE), 2017)
Considering the rising demand for electricity around the world, several technologies have been developed to provide a more efficient and modern power system. In this context, the smart grid concept is related to the integration and management of different power system devices, aiming to provide technical, economic, social and environmental benefits. Thus, the smart meter has become one of the main elements in smart grids and it may provide much more capabilities than the conventional electromechanical and electronic energy meters. Therefore, this paper discusses the main differences between smart and conventional power meters, pointing to the new features, methodologies and applications of modern smart meters. Moreover, this paper deals with the definition of 'smart', introducing possible functionalities and applications that can effectively impact on the understanding of the energy consumption, while allowing to improve power management and energy efficiency.
Keywords: Cognitive meter; Energy meter; Power meter; Smart grid; Smart meter